2017
DOI: 10.1007/s10549-017-4311-8
|View full text |Cite
|
Sign up to set email alerts
|

Host genetic modifiers of nonproductive angiogenesis inhibit breast cancer

Abstract: Collectively, these data suggest that host genetic modifier(s) on RNO3 induce nonproductive angiogenesis that inhibits tumor growth through the DLL4 pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…The RNA-sequencing protocol was previously reported (22,23). Briefly, total RNA was extracted by TRIzol (Thermo Fisher Scientific, Waltham, MA) from the left ventricle tissue of 11-13 weeks old female mock-treated SS and SS.BN3 rats (N = 4-5/group) from a group of rats matched to 1 week post-radiation rats (not reported here, but previously reported).…”
Section: Rna-sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…The RNA-sequencing protocol was previously reported (22,23). Briefly, total RNA was extracted by TRIzol (Thermo Fisher Scientific, Waltham, MA) from the left ventricle tissue of 11-13 weeks old female mock-treated SS and SS.BN3 rats (N = 4-5/group) from a group of rats matched to 1 week post-radiation rats (not reported here, but previously reported).…”
Section: Rna-sequencingmentioning
confidence: 99%
“…We previously reported that the inbred Dahl saltsensitive/Mcwi (SS) rat strain was more sensitive to localized image-guided cardiac radiation than the Brown Norway (BN) strain, and that substitution of chromosome 3 from the BN strain into the SS background (SS.BN3 consomic rats) confers dramatic resistance to radiation-induced cardiac dysfunction when compared to the SS strain (22). Consomic chromosome substitution studies can be used to map complex genetic modifiers of pathophysiologic phenotypes (23)(24)(25)(26). In our previous consomic rat study with the SS strain that was relatively sensitive to localized cardiac radiation when compared to the SS.BN3 consomic strain, the top genetic pathways differentially expressed between SS and SS.BN3 consomic rat ventricles 1 week after radiation included mitochondrial-related genes (22).…”
Section: Introductionmentioning
confidence: 99%
“…Mcs5a influences tumor progression via the immune system (T cells) in a FBXO10 -dependent manner – analogous to a mechanism in human T lymphocytes (Xu et al, 2014) that is associated with human breast cancer risk (Samuelson et al, 2007). The second modifier locus is linked with DLL4 and impacts breast cancer growth and metastasis by inducing dysfunctional angiogenesis (Flister et al, 2017). A good example from the blood cancer field that may be highly relevant for myeloma is research at the US National Cancer Institute that uncovered the TME risk gene Mndal (myeloid cell nuclear differentiation antigen-like).…”
Section: Current Research Gaps and Future Directionsmentioning
confidence: 99%
“…Such immunocompromised strains are labelled as SS IL2Rγ SS.BN# IL2Rγ . Previous studies on mapping of all BN chromosome substitutions in SS indicated the role of chromosome #3 in inhibiting spontaneous tumoigenesis, murine tumor growth and metastasis [24,25]. We recently demonstrated that human triple-negative breast cancer (TNBC) tumors grown in the SS.BN3 IL2Rγ CXM strain had significantly reduced growth and metastatic progression, reduced expression of notch-pathway gene DLL4 responsible for vascular budding, along with a paradoxical increase in tumor blood vessel density, compared to the parental SS IL2Rγ strain.…”
Section: Introductionmentioning
confidence: 99%